Nuclear shape coexistence in 194Hg - Fotiades, N.; Harissopulos, S.; Kalfas, C. A.; Kossionides, S.; Papadopoulos, C. T.; Vlastou, R.; Serris, M.; Sharpey-Schafer, J. F.; Joyce, M. J.; Beausang, C. W.; Dagnall, P. J.; Forsyth, P. D.; et al. (HNPS Advances in Nuclear Physics, 2019)
High spin states in the isotope 194Hg were populated using the 150Nd (48Ca,4n) reaction at a beam energy of 213 MeV. A sequence of dip ole transitions has been observed above 8 MeV excitation energy. Cross-over transitions have also been identified. An interpretation connecting this sequence to a nuclear shape change is attempted. A comparison with similar structures in the neighbouring Hg isotopes is also attempted.